Riding through the silver tsunami: A data driven approach to improve senior citizens’ engagement with community senior activity centres - LAM, Joshua Jie Feng (Institutional Knowledge at Singapore Management University, 2021)
In Singapore, 1 in 4 persons will be elderly by 2030 In preparation for the Silver Tsunami, the Singapore government and community care providers have collaborations to promote active, independent living amongst elders Current implementation of data driven population health is focused on well being indices using data collected from the general population There is no literature on the use of data analytics in assessing elder